2021
DOI: 10.1002/ets2.12329
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Spoken and Written Language Use in Traditional andTechnology‐MediatedLearning Environments

Abstract: A key piece of a validity argument for a language assessment tool is clear overlap between assessment tasks and the target language use (TLU) domain (i.e., the domain description inference). The TOEFL 2000 Spoken and Written Academic Language (T2K‐SWAL) corpus, which represents a variety of academic registers and disciplines in traditional learning environments (e.g., lectures, office hours, textbooks, course packs), has served as an important foundation for the TOEFL iBT® test's domain description inference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(48 citation statements)
references
References 32 publications
(46 reference statements)
4
20
0
Order By: Relevance
“…In order to investigate the language used in TMLEs, Kyle et al (2021) collected a relatively large corpus (4.5 million words) of texts that represent various TMLEs from students and instructors at public universities and from publicly available online courses (i.e., massive open online course or MOOCs). They then used the TMLE corpus and the T2K-SWAL corpus (2.8 million words) to compare and contrast the lexicogrammatical features of language used in written and spoken university registers in technology-mediated and non-technology-mediated learning environments using MDA.…”
Section: The Tmle Projectmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to investigate the language used in TMLEs, Kyle et al (2021) collected a relatively large corpus (4.5 million words) of texts that represent various TMLEs from students and instructors at public universities and from publicly available online courses (i.e., massive open online course or MOOCs). They then used the TMLE corpus and the T2K-SWAL corpus (2.8 million words) to compare and contrast the lexicogrammatical features of language used in written and spoken university registers in technology-mediated and non-technology-mediated learning environments using MDA.…”
Section: The Tmle Projectmentioning
confidence: 99%
“…However, typical academic learning environments have been increasingly technology-mediated (e.g., through the affordances of course management software; Jacoby, 2014;Means et al, 2013), a trend that has increased dramatically due to the COVID-19 pandemic. Recently, Kyle et al (2021) collected a corpus of language encountered in technologymediated learning environments (TMLEs) and compared the linguistic features of spoken and written language across TMLEs and non-TMLEs using multidimensional analysis (MDA; Biber, 1988). Their analysis indicated that TMLEs and non-TMLEs demonstrated similar general patterns of language use across spoken and written modes (e.g., texts in spoken modes tended to include more clausal coordination, contractions, and emphatics while texts in written modes tended to include longer words and more phrasal coordination).…”
mentioning
confidence: 99%
See 3 more Smart Citations